PENGARUH NAA, BAP DAN KOMBINASINYA PADA MEDIA MS TERHADAP PERKEMBANGAN EKSPLAN Sansevieria macrophylla SECARA IN VITRO - Muliati, Muliati; Nurhidayah, Tengku; Nurbaiti, Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of this research is to study the effect of NAA, BAP and their combinations in MS media on the formation of callus and bud morphogenesis of Sansevieria macrophylla explants. The research has been conducted at the Laboratory of Plant Biotechnology, Faculty of Agriculture, University of Riau, from August 2015 to February 2016. The experiment was arranged in a Completely Randomized Design, consisting of 8 treatments and 3 replications. Each treatment consisted of 4 explants of Sansevieria macrophylla. The treatments were application of NAA, BAP and their combinations in MS media : NAA 1 mg/L, NAA 2 mg/L, BAP 1 mg/L, BAP 2 mg/L, NAA 1 mg/L + BAP 1 mg/L, NAA 1 mg/L + BAP 2 mg/L, NAA 2 mg/L + BAP 1 mg/L, NAA 2 mg/L + BAP 2 mg/L . The parameters observed were : the time of callus appearance, colour of callus, texture of callus, time of shoots appearance and the survival bud rate. The data were analyzed with  analysis of variance and the means of treatment were compared by using Duncan’s New Multiple Range Test at 5 % level. The data of callus colour and texture were analyzed descriptively and presented in a tabular form. The result showed that the addition of BAP 2 mg/L in MS media gave the earliest time of callus appearance and BAP 1mg/L gave the highest percentage of survival bud rate. The combination of NAA 1 mg/L + BAP 1 mg/L  gave the earliest time of shoots appearance of Sansevieria macrophylla explants in MS media.Keywords:Sansevieria macrophyllaExplants, NAA, BAP and in vitro